2016
DOI: 10.1007/s41062-016-0003-1
|View full text |Cite
|
Sign up to set email alerts
|

An efficient approach for assessing the seismic soil structure interaction effect for the asymmetrical pile group

Abstract: All of the civil engineering structures involve some type of structural element which is in direct contact with soil. To estimate the accurate response of the superstructure it is necessary to consider the response of the soil supporting structure, and is well explained in the soil structure interaction analysis. Many attempts have been made to model the SSI problem numerically; however the soil nonlinearity, foundation interfaces and boundary conditions make the problem more complex and computationally costli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…This method is able to simultaneously consider with accuracy the behavior of both the soil and the structure. Several researchers [11,12,16,17,22,[27][28][29] have studied the effect of the soil-pile-structure interaction on the behavior of buildings, adopting the direct method to get realistic analysis. In this study, the direct method is employed because of its adaptability to deal with complex geometries and material properties.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is able to simultaneously consider with accuracy the behavior of both the soil and the structure. Several researchers [11,12,16,17,22,[27][28][29] have studied the effect of the soil-pile-structure interaction on the behavior of buildings, adopting the direct method to get realistic analysis. In this study, the direct method is employed because of its adaptability to deal with complex geometries and material properties.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that the lateral displacements of the floating pile foundations are greater than the ones of the structure with a fixed-base condition, but are more reduced than the shallow foundation case due to the rocking components. Badry and Satyam [16] analyzed the dynamic response of a 3D nonlinear finite element system that consisted of an L-shape 11-storey building supported by a pile foundation with homogeneous soil conditions. The research included the applicability of the equivalent pier methods for the asymmetrical pile groups and the SSI effect of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Seismic soil-structure interaction of a pile group was studied using equivalent pier method (EPM) by Badry et al [9]. The study was conducted on an axisymmetric multistoried building and the peak response of the building under fixed base condition and flexible base condition were studied.…”
Section: Numerical Investigationmentioning
confidence: 99%
“…8 Building pile system supported by the free-field ground through winkler type soil model [50] Fig. 9 Sketch of bending moment distribution in fixed head pile group [105] the difference in maximum bending moment and pile top deflection in comparison to the other's methods. Many researchers have performed the finite element analysis using the software PLAXIS 3D Foundation using embedded pile element and the analysis results are in good agreement with the pile load test conducted by various researchers.…”
Section: Engineering Bedrockmentioning
confidence: 99%
“…For example, Mostafa and EI Naggar [14] proposed a method to analyse the dynamic lateral response of pile group under harmonic excitation. Basack and Nimbalkar [15] developed a numerical model based on a two-dimensional (2D) dynamic finite-element (FE) approach.. For cases when superstructures were considered, the seismic response of the pile-soil-structure interaction were studied experimental [16][17][18][19] and numerically [20][21][22][23][24][25]. As n-g centrifuge experiment, liquefication study and numerical simulation beyond the scope of this paper, so they are not discussed in this paper.…”
Section: Introductionmentioning
confidence: 99%